Controllable preparation of chitosan oligosaccharides via a recombinant chitosanase from marine Streptomyces lydicus S1 and its potential application on preservation of pre-packaged tofu - Chen, Hao; Lin, Bilian; Zhang, Rui; Gong, Zhouliang; Wen, Ming; Su, Weiming; Zhou, Jinsong; Zhao, Liangzhong; Wang, Jianrong (Frontiers in Microbiology, 2022)
Chitosan oligosaccharides (COSs) are widely applied in many areas due to its various biological activities. Controllable preparation of COSs with desired degree of polymerization (DP) via suitable chitosanase is of great value. Herein, a novel glycoside hydrolase family 46 chitosanase (SlCsn46) from marine Streptomyces lydicus S1 was prepared, characterized and used to controllably produce COSs with different DP. The specific activity of purified recombinant SlCsn46 was 1008.5 U/mg. The optimal temperature and pH of purified SlCsn46 were 50 °C and 6.0, respectively. Metal ions Mn2+ could improve the stability of SlCsn46. Additionally, SlCsn46 can efficiently hydrolyse 2% and 4% colloidal chitosan to prepare COSs with DP 2–4, 2–5 and 2–6 by adjusting the amount of SlCsn46 added. Moreover, COSs with DP 2–4, 2–5 and 2–6 exhibited potential application value for prolonging the shelf-life of pre-packaged Tofu. The water-holding capacity (WHC), sensorial properties, total viable count (TVC), pH and volatile base nitrogen (TVB-N) of pre-packed tofu incorporated with 4 mg/mL COSs with DP 2–4, 2–5 and 2–6 were better than those of the control during 15 days of storage at 10 °C. Thus, the controllable hydrolysis strategy provides an effective method to prepare COSs with desired DP and its potential application on preservation of pre-packed tofu.